Blood Pressure Variability and Cognitive Function: a Scoping Review - Nur Fazidah, Asmuje; Sumaiyah, Mat; Myint, Phyo Kyaw; Tan, Maw Pin * (Springer, 2022)
Purpose of review: To conduct a scoping review of articles which have evaluated BPV and cognitive function. Articles with keywords, titles or abstracts containing the terms 'cognitive' OR 'cognition' OR 'dementia' AND 'blood pressure variability' were identified from CINAHL, Medline, PMC and Web of Science.